2021
DOI: 10.1371/journal.pone.0245444
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between social support, stressful events, and menopause symptoms

Abstract: Many women going through the menopausal transition experience vasomotor symptoms (VMS), and research has shown that there is a large amount of variation in their frequency and severity. Many lifestyle factors have been found to co-vary with VMS, including the level of social support received by the woman, and how stressed she is. Stress is well documented to worsen menopause symptoms, and there is some evidence that support eases them; however, there is little research into whether support is an effective buff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 73 publications
(103 reference statements)
1
25
0
Order By: Relevance
“…Social and societal explanations for the experience of complaints typically associated with menopause in autistic women should also be considered. A lower impact of the menopausal transition is associated with stronger social support during stressful life events (Arnot et al, 2021), greater physical fitness, better coping strategies, and better sleep quality (Duffy et al, 2013). All these factors are generally rated lower in those with an ASC (Bishop-Fitzpatrick & Rubenstein, 2019;Ee et al, 2019;Hirvikoski & Blomqvist, 2015;Maxwell-Horn & Malow, 2017), suggesting that these could also impact the experience of menopause in autistic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Social and societal explanations for the experience of complaints typically associated with menopause in autistic women should also be considered. A lower impact of the menopausal transition is associated with stronger social support during stressful life events (Arnot et al, 2021), greater physical fitness, better coping strategies, and better sleep quality (Duffy et al, 2013). All these factors are generally rated lower in those with an ASC (Bishop-Fitzpatrick & Rubenstein, 2019;Ee et al, 2019;Hirvikoski & Blomqvist, 2015;Maxwell-Horn & Malow, 2017), suggesting that these could also impact the experience of menopause in autistic individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Having persistent and/or troublesome VMS and sleep problems can make women feel stressed and irritable, which in turn can exacerbate menopausal symptoms. An estimated 9–10% of women report an increase in psychological symptoms, including depressed mood and/or anxiety, during the menopause transition (Almeida et al, 2016 ; Mishra & Kuh, 2012 ), which tends to be relatively transient, and is associated with troublesome VMS, current stress, low self‐esteem, and hormone fluctuations (Arnot, Emmott, & Mace, 2021 ; Campbell, Dennerstein, Finch, & Szoeke, 2017 ; Willi, Süss, Grub, & Ehlert, 2021 ). Longer duration of VMS has been linked with higher levels of perceived stress (Avis et al, 2015 ); acute psychological stress has been shown to provoke VMS (Swartzman, Edelberg, & Kemmann, 1990 ); there is also some evidence of altered physiological stress responsivity in women with VMS (Nathan et al, 2020 ).…”
Section: Figurementioning
confidence: 99%
“…One of the factors that have recently been a matter of concern is the 1 2 perceived social support among females. Research highlights that women need social support to cope and adapt to the menopausal symptoms in this stressful period of their life, and this may help control their symptoms [11,12]. The severity of symptoms may have a negative impact on daily activity and quality of life.…”
Section: Introductionmentioning
confidence: 99%